ENVIORNMENTAL ETHICS TO HOLISTIC ONTOLOGY: A Naessian Approach - Francis, Jith (Journal of Dharma, 2014)
Deep ecological movement, started in 1972 by distinguished Norwegian philosopher Arne Naess, is founded on three basic principles: a scientific insight into the interrelatedness of all systems of life on Earth together with the rejection of anthropocentrism, the need of self realization, identifying with the whole, and Holistic Ontology. If we realize the universe as a self, where we find the interconnectedness of ourselves with the universe then that would involve a radical change of environmental ethics to an environmental metaphysics. That in turn would make our ways of living more consistent with the well being of life on earth. The Deep Ecology, proposed by Arne Naess helps the readers to have a holistic approach to our mother earth and to the environment.